THE PORTRAYAL OF WORKING MOTHEIR IN I DON'T KNOW HOW SHE DOES IT BY ALISON PEARSON - Dini Lesmanawati, - (2008)
This research paper is entitled "The Portrayal of Working Mother in I Don't Know How She Does It by Allison Pearson". The research is designed to answer the following question: "How is the working mother portrayed in the Allison Pearson novel from the perspective of liberal feminism". In order to answer the formulated research question above, the study uses qualitative approach and descriptive method. This research paper focuses on the portrayal of working mother portrayed on the novel which is based on its characteristics. Afterward, all the data collected are analyzed by means of liberal feminist perspective by Wollstonecraft, Taylor, Mill and Friedan. The results of this research show that the portrayal of working mother does indicate the spirit of liberal feminism. The woman in the novel has succeeded in liberating her self in the patriarchal society and the woman has also achieved the equality in all aspect of her life.